Metamórficas: Processos de Comprovisação a Partir de Violões em Microtonalidade Smetakiana e de Indeterminações Eletroacústicas em Partituras Gráficas (Orfeu, 2025)
This research is part of an ongoing investigation into contemporary comprovisation, this time exploring how a phenomenology of comprovisational creation could emerge from a decolonial perspective. As a first step in this inquiry, the adaptation for microtonal guitars and tape of a piece by the author George Cristian Vilela Pereira—alongside collaborators Vladimir Bomfim and Heitor Dantas—entitled Metamórficas, for tape and various freely chosen instruments, composed in 2020, is being documented. From this adaptation, several questions arose regarding its foundation, and it was observed that there is a comprovisation within a specific notation perspective in its graphic scoring, along with implications related to musical freedom, instrumental articulations, and structuring. Microtonalism, in both discrete and continuous approaches, has been systematically applied using two VMS (Smetakian microtonal guitars) and a folk guitar in hexachordal tuning, as well as through a photoelectronic synthesizer, Virtual ANS. It is noted here that there is a connection not only with the VMS but also with the structural non-idiomatic improvisation practices currently being developed to adapt Metamórficas.